2019
DOI: 10.1093/hmg/ddz107
|View full text |Cite
|
Sign up to set email alerts
|

Altered calcium dynamics and glutamate receptor properties in iPSC-derived motor neurons from ALS patients with C9orf72, FUS, SOD1 or TDP43 mutations

Abstract: The fatal neurodegenerative disease amyotrophic lateral sclerosis (ALS) is characterized by a profound loss of motor neurons (MNs). Until now only riluzole minimally extends life expectancy in ALS, presumably by inhibiting glutamatergic neurotransmission and calcium overload of MNs. Therefore, the aim of this study was to investigate the glutamate receptor properties and key aspects of intracellular calcium dynamics in induced pluripotent stem cell (iPSC)-derived MNs from ALS patients with C9orf72 (n = 4 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…Eigengene classification identifies the cells in these cultures with whole spinal cord with 83% probability. All cell lines differentiated into Islet-1 positive MNs with a similar efficiency of approximately 50% (Figure 1F), and which we had previously demonstrated using this protocol as being electrophysiologically functional (Bursch et al, 2019). Since cultures expressed very high levels of spinal neuronal markers and were enriched with MNs, we hereafter refer to these cultures as iPSC-derived SNs.…”
Section: Resultssupporting
confidence: 71%
“…Eigengene classification identifies the cells in these cultures with whole spinal cord with 83% probability. All cell lines differentiated into Islet-1 positive MNs with a similar efficiency of approximately 50% (Figure 1F), and which we had previously demonstrated using this protocol as being electrophysiologically functional (Bursch et al, 2019). Since cultures expressed very high levels of spinal neuronal markers and were enriched with MNs, we hereafter refer to these cultures as iPSC-derived SNs.…”
Section: Resultssupporting
confidence: 71%
“…The authors suggested that calcium homeostasis in addition to DNA damage and oxidative stress could be among major molecular underpinnings for a significant proportion of unexplained FTD etiology 36 . In separate studies, calcium dysregulation was reported to contribute to neurodegeneration in iPSC-derived neurons from FTD patients 38 and ALS patients 39 . In C9ORF72 iPSC-derived motor neurons from ALS and FTD patients, decreased cell survival correlated with calcium homeostasis, suggesting a novel pathogenic link between C9ORF72, dysregulated calcium signaling and altered proteostasis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in recent years, investigators have tried to elaborate a link between ALS/FTD gene mutations, including C9orf72 repeat expansions, and neuronal hyperexcitability/excitotoxicity mechanisms. The expression of kainate receptors and voltage-gated Ca 2+ channels in iPSC-derived motor neurons, cell surface levels of the NMDA receptor GluN1 and the AMPA receptor GluR1 on neurites, and dendritic spines of iMNs from C9orf72 ALS/FTD patients are found to be markedly elevated compared to controls [34,52,53]. Glutamate receptors also accumulate at postsynaptic densities in these neurons [34].…”
Section: Loss Of Function Mechanismsmentioning
confidence: 95%